Aurora-A is a novel predictor of poor prognosis in patients with resected lung adenocarcinoma - Zeng, Bo; Lei, Yiyan; Zhu, Haoshuai; Luo, Shenyuan; Zhuang, Mei; Su, Chunhua; Zou, Jianyong; Yang, Lei; Luo, Honghe (Chinese Journal of Cancer Research; Vol 26, No 2 (April 26, 2014): Chinese Journal of Cancer Research, 2014)
Background: The Aurora-A (Aur-A) gene, a key regulator of mitosis, has been proved as an oncogene in a variety of cancers. The Aur-A overexpression has been proved correlated with aggressiveness of cancer cells. However, the frequency of Aur-A protein overexpression, as well as its association with clinicopathologic parameters and prognosis remain unclear in lung adenocarcinoma (ADC). This study tried to clarify the clinical significance of Aur-A in patients with resected lung ADC. Patients and methods: A total of 142 informative patients with surgically resected lung ADC and 20 normal lung tissues were enrolled. Western blot and immunohistochemistry (IHC) were utilized to assess protein expression of Aur-A. Result: The expression of Aur-A was elevated in most of tumor tissues compared with the adjacent tissues by western blot. The IHC results showed that Aur-A protein was over-expressed in 98 of 142 (69.0%) tumor sections, while Aur-A was low-expressed in all normal lung sections. A positive correlation between Aur-A overexpression rate and ascending pathologic stages was observed (P